Da'wah Bil Hikmah in the Implementation of the Massoro Baca Tradition in Lasare village, Pangkep Regency, South Sulawesi - Andi Hasriani; St Samsudduha (Journal of Research and Multidisciplinary, 2021)
This research discusses the Da'wah Bilin the tradition HikmahMassuro Mabbaca. The goal to be achieved is to know the implementation of rituals carried out in the tradition Massuro Mabbaca as well as to know the implementation of dakwah bil hikmah in the implementation of the tradition Massuro Mabbaca . The Tradition masuro mabbaca has been carried out by the community from generation to generation so that it is hoped that in its implementation there will be no mixing of religious teachings and customs. There is an awareness in the community not to make this tradition an obligation but that it is purely a culture. research reading massuro This is located in Lasare Village, Bone Village, Segeri District, Pangkep Regency. In data collection, a qualitative approach is used because this type of qualitative research has an inductive nature, namely the development of concepts based on existing data, following a flexible research design according to the context. The steps taken are to determine the research location, focus, research, research subjects, data collection methods, data analysis and continue with drawing conclusions. The conclusions obtained in this study is,tradition mabbaca massuro is tradition carried from generation to generation that has a value of philosophy as well as the value of propaganda in the implementation, describes nflaivalues culture contained in the procession massuro mbaread at once an expression of gratitude for all the blessings that Allah has given. However, the implementation of this tradition still requires monitoring and guidance from the government and religious leaders so that people are able to distinguish between traditions that have Islamic values and traditions that are pure as culture.